PENGARUH MANAJEMEN MODAL KERJA DAN SOLVABILITAS TERHADAP KINERJA PERUSAHAAN - Sucinia Silfina; Hendra Gunawan (Politeknik Negeri Batam, 2019)
This study examines the effect of working capital management and solvency on the performance of manufacturing companies. Data samples were taken from the OSIRIS database of 74 manufacturing companies for the period 2010-2015. The effect of independent variables such as the current ratio, quick ratio, cash ratio and the company's debt to equity ratio partially to return on assets was examined using panel data analysis methods. This study shows that the current ratio, and the debt to equity ratio have an effect on and significantly affect the company's performance. Quick ratio and cash ratio do not have a significant effect on company performance. Future studies are expected to use other independent variables and measurement of company performance can also be proxied by other ratios.